The Practice of Social Support and Self-Adjustment: Minangkabau Students in Yogyakarta - Nurhasanah; Lessy, Zulkipli (LP2M UIN Sunan Kalijaga, 2022)
This research was mainly based on the number of Minangkabau students who migrated and continued their studies in Yogyakarta so that they required self-adjustment that was different from their place of origin. The purpose of this study is to discover the relationship between social support and self-adjustment among Minangkabau students in Yogyakarta. The null hypothesis states that there is a significant positive relationship between social support and self-adjustment. The higher the social support rises, the higher the individual adjustment makes. The lower the social support obtained, the lower the adjustment will be. The subjects of this study were Minangkabau students in Yogyakarta. The sampling technique in this study used the accidental sampling technique. The method used in this study is quantitative, while the data collection tools used are the social support scale and self-adjustment scale, the data analysis method using analysis prerequisite testing (normality test and linearity test) and hypothesis testing using the correlation of Pearson's product moment with the help of SPSS 23.0 for windows. Based on the research results that have been obtained, it can be seen and concluded that the hypothesis proposed in this study can be accepted, as evidenced by the results of the correlation coefficient of 0.502 and a significance value of 0.000 (p <0.05). This shows that there is a positive and significant relationship between social support and adjustment to Minangkabau students in Yogyakarta. [Penelitian ini dilatarbelakangi oleh banyaknya mahasiswa Minangkabau yang merantau dan melanjutkan studi mereka di Yogyakarta sehingga membutuhkan suatu penyesuaian diri yang berbeda dengan tempat asalnya. Penelitian ini bertujuan untuk mengetahui bagaimana hubungan dukungan sosial dengan penyesuaian diri mahasiswa Minangkabau yang berada di Yogyakarta. Hipotesis awal pada penelitian ini adalah terdapat hubungan positif yang signifikan antara dukungan sosial dengan penyesuaian diri. Semakin tinggi dukungan sosial maka semakin tinggi pula penyesuaian diri individu. Sebaliknya, semakin rendah dukungan sosial yang didapat maka semakin rendah pula penyesuaian dirinya. Subyek penelitian ini adalah mahasiswa Minangkabau yang ada di Yogyakarta. Teknik pengambilan sampel dalam penelitian ini menggunakan teknik accidental sampling. Metode yang digunakan dalam penelitian ini adalah kuantitatif sedangkan alat pengumpulan data yang digunakan adalah skala dukungan sosial dan skala penyesuaian diri, metode analisis data dengan menggunakan pengujian prasyarat analisis (uji normalitas dan uji linearitas) dan uji hipotesis dengan menggunakan korelasi dari Pearson product moment dengan bantuan SPSS 23.0 for windows. Berdasarkan hasil penelitian yang telah diperoleh, maka dapat dilihat dan disimpulkan bahwa hipotesis yang diajukan dalam penelitian ini dapat diterima, dibuktikan dengan hasil koefisien korelasinya sebesar 0,502 dan nilai signifikansi sebesar 0,000 (p<0,05). Hal tersebut menunjukkan bahwa adanya hubungan yang positif dan signifikan antara dukungan sosial dengan penyesuaian diri pada mahasiswa Minangkabau di Yogyakarta.]